2020
DOI: 10.1371/journal.pgen.1009088
|View full text |Cite
|
Sign up to set email alerts
|

Genetic compensation prevents myopathy and heart failure in an in vivo model of Bag3 deficiency

Abstract: Mutations in the molecular co-chaperone Bcl2-associated athanogene 3 (BAG3) are found to cause dilated cardiomyopathy (DCM), resulting in systolic dysfunction and heart failure, as well as myofibrillar myopathy (MFM), which is characterized by protein aggregation and myofibrillar disintegration in skeletal muscle cells. Here, we generated a CRISPR/Cas9-induced Bag3 knockout zebrafish line and found the complete preservation of heart and skeletal muscle structure and function during embryonic development, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 44 publications
(96 reference statements)
1
26
0
Order By: Relevance
“…For example, BAG3 belongs to the BAG protein family acting as a chaperone molecular via physical interaction with Hsp70, HSPBs. It was shown that mutated BAG3 caused DCM, leading to systolic dysfunction, HF, and myofibrillar myopathy ( Sturner and Behl, 2017 ; Diofano et al, 2020 ). BAG2 was also a member of the human BAG protein family and is expressed in brown adipose, lung, heart, and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BAG3 belongs to the BAG protein family acting as a chaperone molecular via physical interaction with Hsp70, HSPBs. It was shown that mutated BAG3 caused DCM, leading to systolic dysfunction, HF, and myofibrillar myopathy ( Sturner and Behl, 2017 ; Diofano et al, 2020 ). BAG2 was also a member of the human BAG protein family and is expressed in brown adipose, lung, heart, and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTOR signaling improves cardiac function and hence, could be a target gene for therapeutic treatment of DCM caused by mutations in Bag3 ( Ding et al, 2019 ). However, CRISPR-Cas9 generated knockout of bag3 fails to show a DCM phenotype in adult zebrafish due to compensation by bag2 ( Diofano et al, 2020 ). These studies also demonstrate how genetic compensation may influence the penetrance of disease-causing mutations in vivo , and underscores the importance of comparing various gene-editing techniques and solving possible discrepancies.…”
Section: Genetic Heart Failure Modelsmentioning
confidence: 99%
“…Diofano et al investigated the consequences of CRISPR/Cas9-induced zebrafish knockout of co-chaperone Bcl2-associated athanogene 3 ( bag3 ) wherein the bag3 morphant has been documented to cause cardiovascular defects including dilated cardiomyopathy and myofibrillar myopathy [ 37 ]. The authors found that the bag3 homozygous mutant had a surprisingly complete and preserved skeletal muscle structure and heart formation despite confirmation of substantially reduced bag3 mRNA levels.…”
Section: Gene Compensation Examplesmentioning
confidence: 99%
“…The injection of bag2 splice-blocking morpholino into bag3 mutant embryos recapitulated the cardiovascular defects witnessed in the bag3 morphant. Diofano et al further demonstrated that the inhibition of the nonsense-mediated mRNA decay pathway via NMD essential gene upf1 knockdown in bag3 mutants prevented the degradation of mutant bag3 mRNA, foiling compensation by bag2 and leading to the expected heart and skeletal muscle defects [ 37 ].…”
Section: Gene Compensation Examplesmentioning
confidence: 99%